2010
DOI: 10.5194/acp-10-10849-2010
|View full text |Cite
|
Sign up to set email alerts
|

A refinement of the emission data for Kola Peninsula based on inverse dispersion modelling

Abstract: Abstract. The study reviews the emission estimates of sulphur oxides (SO x ) and primary particulate matter (PM) from the major industrial sources of Kola Peninsula. Analysis of the disagreements between the existing emission inventories for the Kola region combined with forward and inverse ensemble dispersion modelling, analysis of observation time-series and model-measurement comparison showed that the emission of the Nikel metallurgy plant was missing or strongly under-estimated in the major European emissi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…The gap is most pronounced for fine aerosol particles (middle panels), which are likely to be responsible for the snow pollution. The pattern also agrees with the location of main air pollution sources in the region (Prank et al, 2010): mining and refining industries located at Kola Peninsula.…”
Section: Origins Of Snow Impuritiessupporting
confidence: 73%
See 1 more Smart Citation
“…The gap is most pronounced for fine aerosol particles (middle panels), which are likely to be responsible for the snow pollution. The pattern also agrees with the location of main air pollution sources in the region (Prank et al, 2010): mining and refining industries located at Kola Peninsula.…”
Section: Origins Of Snow Impuritiessupporting
confidence: 73%
“…For quantitative and comparatively accurate assessment in case of limited observational information, the so-called "footprint" computations can be used (e.g., Prank et al, 2010). This approach is based on solving the adjoint dispersion equation for, e.g., an isolated episode registered by a single measurement device.…”
Section: Source Identification For Snow Impuritiesmentioning
confidence: 99%
“…The idea of the method is to explicitly compute the sensitivity of the observed values to emission fl uxes, chemical transformations and meteorological processes, which can affect the particular observation. Saarikoski et al 2007 ;Prank et al 2008Prank et al , 2010 , and for the regional-scale source apportionment of the observed pollen (Veriankaité et al 2010 ;So fi ev et al 2006a, b ;Siljamo et al 2008b ) . Saarikoski et al 2007 ;Prank et al 2008Prank et al , 2010 , and for the regional-scale source apportionment of the observed pollen (Veriankaité et al 2010 ;So fi ev et al 2006a, b ;Siljamo et al 2008b ) .…”
Section: Inverse Studies and Analysis Of Observational Resultsmentioning
confidence: 99%
“…The smelter industry in Kola Peninsula is not only the most important source of anthropogenic atmospheric SO 2 in the Finnish eastern Lapland but also the largest or second largest source in the entire Arctic domain (Benkovitz et al, 1996;Prank et al, 2010), depending on the definition of the Arctic boundaries. During the past 2 decades, sulfur emissions from the Kola area have decreased distinctively, although they are still larger than those of entire Finland (Paatero et al, 2008).…”
Section: E-m Kyrö Et Al: Effect Of Decreasing Sulfur Emissions Fromentioning
confidence: 99%